Is mitochondrial dysfunction a putative marker of cardiometabolic disease in people living with HIV? - Mokoena, Kheya Reatlegile (Stellenbosch : Stellenbosch University, 2025)
Mokoena, K. 2025. Is mitochondrial dysfunction a putative marker of cardiometabolic disease in people living with HIV? Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/18e3a6ac-5237-49e5-bc6c-4bc507a44998